The Complete Prose of T. S. Eliot: The Critical Edition : The Perfect Critic, 1919-1926 - Eliot, T. S. (Thomas Stearns), 1888-1965 (Faber and Faber, 2014)
The Complete Prose of T.S. Eliot gathers for the first time in one place the collected, uncollected, and unpublished prose of one of the most prolific writers of the twentieth century. The result of a multi-year collaboration among Eliot's Estate, Faber and Faber Ltd., Johns Hopkins University Press, the Beck Digital Center of Emory University, and the Institute of English Studies, University of London, this eight-volume critical edition dramatically expands access to material that has been restricted or inaccessible in private and institutional collections for almost fifty years.